Examining the osteological paradox: Skeletal stress in mass graves versus civilians at the Greek colony of Himera (Sicily). Issue 1 (3rd September 2018) - Kyle, Britney; Reitsema, Laurie J.; Tyler, Janelle; Fabbri, Pier Francesco; Vassallo, Stefano
Abstract: Objectives: Bioarchaeologists interpret skeletal stress as evidence of resilience or frailty, where absence of lesions might result from lack of exposure to pathogens (i.e., good health) or extreme vulnerability (i.e., selection). We examine physiological stress in two skeletal series from Greek Himera: (1) nine mass graves from the battles of Himera (480 and 409 BCE) and (2) Himeran civilians (648‐409 BCE). Civilians are assumed to have died from multiple causes, including ill health leading to their deaths. Individuals from the battles presumably died while in relatively good health, in battle. More skeletal stress among civilians than battle casualties would support the idea that skeletal stress is a sign of frailty at Himera. We compare variation in skeletal stress between and among civilians and battle casualties. Materials and methods: Cribra orbitalia, porotic hyperostosis, linear enamel hypoplasia (LEH), and sub‐periosteal new bone formation, were examined in 474 individuals (mass graves n  = 64; civilians n  = 410). Results: Chi‐square tests showed significantly higher prevalence of LEH ( p  = 0.04) and sub‐periosteal new bone formation ( p  = 0.05) among young and mid‐aged adult male civilians than mass grave casualties. Skeletal stress was also lower in the earlier battle, and varied among civilians with burial style. Discussion: Our findings generally support the hypothesis that skeletal stress is evidence of frailty (i.e., leading to greater risk of mortality). However, the relationship between stress and frailty is complicated by social factors, when considering historical context. In particular, a possible "soldier‐class" may have experienced less stress than the overall civilian population.